2019
DOI: 10.1029/2019ja026782
|View full text |Cite
|
Sign up to set email alerts
|

Features of Storm‐Induced Ionospheric Irregularities From Ground‐Based and Spaceborne GPS Observations During the 2015 St. Patrick's Day Storm

Abstract: During geomagnetic disturbances, the solo or combined effect of prompt penetration electric fields (PPEFs) and disturbance dynamo electric fields (DDEFs) alters radically regular pattern of equatorial plasma bubbles (EPBs) occurrence. The severe 17-18 March 2015 storm is an excellent event to trace how the storm reshapes EPB generation at all longitudinal sectors. We present results of a comprehensive analysis of storm-induced EPBs based on combination of in situ and remote sensing techniques including 6,100+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 59 publications
4
42
0
Order By: Relevance
“…One can spot some differences between the ROTI and RODI structures during stronger events; however, it should be remembered that GNSS and Swarm observations have different spatial resolutions and observation intervals, which may result in different sensitivities depending on the structures’ scale and velocity [ 35 ]. Additionally, space-borne observations obtained with Swarm are tied to the orbit altitude and therefore may not reveal all structures [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…One can spot some differences between the ROTI and RODI structures during stronger events; however, it should be remembered that GNSS and Swarm observations have different spatial resolutions and observation intervals, which may result in different sensitivities depending on the structures’ scale and velocity [ 35 ]. Additionally, space-borne observations obtained with Swarm are tied to the orbit altitude and therefore may not reveal all structures [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, despite being an equinoctial event, the storm effects exhibited large hemispheric differences that were attributed to neutral composition changes. The storm's regional effects were also reported extensively, such as TIDs in the European‐African sector (e.g., Amaechi et al, ; Borries et al, ) and over North and South America (Figueiredo et al, ), the effects of PPEF over India (Tulasi Ram et al, ) and in the Asian‐Australian sector (Kuai et al, ), equatorial ionospheric disturbances over southern Asia (Jiang et al, ; Spogli et al, ), the TOI structure (Liu et al, ) and the SED plume (Zhang et al, ) over North America, positive and negative storm phases in the mid‐ and low‐latitude regions (Fagundes et al, ; Nava et al, ), ionospheric irregularities at high latitudes (Cherniak et al, ; Cherniak & Zakharenkova, ; Prikryl et al, ) and in the Latin American sector (Barbosa et al, ), and the formation of equatorial plasma bubbles (Carter et al, ; Kil et al, ; Patra et al, ; Zakharenkova et al, ).…”
Section: Introductionmentioning
confidence: 91%
“…For example, the presence of westward PPEF/DDEF at about 18:00 UT (LT = UT + 3 h) on 17 March 2015 acted to suppress the PRE, thereby inhibiting irregularities. Zakharenkova et al (2019) observed intense postsunset equatorial plasma bubble (EPB) irregularities using measurements from SWARM satellite and ground-based GNSS along with stronger depletions in the Communications/Navigation Outage Forecasting System ion density over East Africa on 16 March 2015 and complete inhibition on 17 March during the main phase while DDEFs were active. In addition, westward electric field that had developed around 20:00 UT on 14 July 2012 acted to reduce the evolution of irregularities activity.…”
Section: Discussionmentioning
confidence: 99%
“…February 2014 and a prolonged suppression thereafter, over Bahir Dah, while Zakharenkova et al (2019) observed a complete inhibition of EPBs using SWARM and Communications/Navigation Outage Forecasting System observations in conjunction with GNSS ROTI maps on 18 March 2015. It is important to note that the duration of irregularities inhibition lasted longer during the superstorm of March 2015 (3 days) than the other storms (1-2 days).…”
Section: Earth and Space Sciencementioning
confidence: 92%